Correlating Between Demographic Distribution and Hematological Parameters in Samples of Iraqi Patients with Colorectal Cancer - Azeez, Rasha Abbas; Suha Abdul-Khaliq Al-Jowari; Hayder Jamal Mahmood (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
The current study found no statistically significant difference in gender or age values between the colorectal cancer (n = 41), colitis (n = 19), or control groups (n = 20), despite the fact that the incidence rate of Colorectal Cancer (CRC) increased significantly with age. In addition, the data showed that alcohol raises the risk by 60.98% in the colorectal adenocarcinoma group who drank alcohol, and the male: female ratio indicated that the majority of patients with early-onset CRC were male patients compared to females. Statistically significant (P≤0.05) differences were found between CRC patients, colitis patients, and control participants who smoked. Furthermore, no significant variations in occupational exposures linked to an elevated risk of CRC were seen between study groups. One of the most fundamental peripheral blood biochemical tests, Hemoglobin (Hb) (g/dL), Red  blood cell count (RBC) (×106 cells/µL), and White blood cell count (WBC) (×103 cells/µL), were used to effectively indicate abnormalities of infection and anemia and improve the accuracy of CRC detection. There were significant differences (P≤0.05) between males and females in W.B.C. count, RBC, and Hb in all types of research groups when compared with the conventional pathological test of tumor lesions. Student's t-test, Fisher's exact test, one-way ANOVA with Hochberg GT2 and Games-Howell tests, and chi-square tests were among the statistical tests used. The diagnostic prediction for CRC early screening was constructed using a panel of commonly used hematological markers, which may serve as useful adjuncts in CRC screening.